Historisising twentieth-century historiography - Liakos, Antonis (Historein, 2017)
The twentieth century has been described as a dark century of wars, holocausts, death and pain. This is true, but it is only a partial image of the century. This article discusses five major challenges and their relations to historiography: a) the disintegration of empires, decolonisation and the rise of new nations; b) the impact of world wars (genocides, revolutions, totalitarian regimes); c) the boom in technoscience and the digital era; d) the ascent of rights, the transformation of gender relations and mass literacy; and e) globalisation. These changes were experienced by three generations of historians. The first generation appeared before the First World War, the second from 1918 to 1970 and the third from 1970. The question we pose is: has the history of historiography responded to these challenges or does it also have its internal logic? And how has it responded?